Education for Sustainable Development: Raising Environmental Awareness in Schools - Salima Meherali (Rahis Cendekia Indonesia, 2025)
This study explores the role of Education for Sustainable Development (ESD) in raising environmental awareness among school students. Amid growing global environmental challenges, schools have a critical responsibility to equip young learners with the knowledge, skills, and values necessary for sustainable living. Using a qualitative descriptive approach, data were collected through interviews, focus group discussions, classroom observations, and document analysis across five schools committed to sustainability education. Findings reveal that integrating environmental themes across curricula and promoting extracurricular activities effectively enhance students’ understanding and engagement with environmental issues. Students reported positive behavioral changes, demonstrating increased environmental responsibility both inside and outside school. However, challenges such as limited teacher training, insufficient resources, and competing academic priorities were identified as barriers to effective implementation. The study underscores the need for systemic support, including professional development, resource allocation, and policy integration, to strengthen the impact of ESD in schools. Ultimately, this research highlights the transformative potential of education to foster environmental stewardship and contribute to a sustainable future.